2015
DOI: 10.1039/c5sc01886b
|View full text |Cite
|
Sign up to set email alerts
|

A T-shaped Ni[κ2-(CF2)4–] NHC complex: unusual Csp3–F and M–CFbond functionalization reactions

Abstract: The reactivity of this T-shaped perfluoronickelacyclopentane–NHC complex with Lewis- and Brønsted acids is enhanced vs. 4-coordinate variants by its low coordination number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…The structure is symmetric within the estimated standard deviation, with the two Ni-Nhydrazone bond lengths being 1.843(4) Å and 1.843( 7 While the DHP scaffold may have some electronic influence in enforcing a T-shaped geometry in 1, this coordination is likely facilitated by steric crowding from the tBu groups as well. [53][54][55][56][57] This complex is analogous to the previously published [ Ph,Tol DHP • ]Ni T-shaped complex which was assigned as a high spin S = 1 Ni(II) center antiferromagnetically coupled to a ligand-based radical based on structural and spectroscopic data. The bond lengths in 1 are very similar to those in [ Ph,Tol DHP • ]Ni with both the Ni-N bond distances and the bond lengths within the ligand backbone nearly identical between the two structures.…”
Section: Synthesis and Electronic Structure Of A T-shaped Ni Complexsupporting
confidence: 80%
“…The structure is symmetric within the estimated standard deviation, with the two Ni-Nhydrazone bond lengths being 1.843(4) Å and 1.843( 7 While the DHP scaffold may have some electronic influence in enforcing a T-shaped geometry in 1, this coordination is likely facilitated by steric crowding from the tBu groups as well. [53][54][55][56][57] This complex is analogous to the previously published [ Ph,Tol DHP • ]Ni T-shaped complex which was assigned as a high spin S = 1 Ni(II) center antiferromagnetically coupled to a ligand-based radical based on structural and spectroscopic data. The bond lengths in 1 are very similar to those in [ Ph,Tol DHP • ]Ni with both the Ni-N bond distances and the bond lengths within the ligand backbone nearly identical between the two structures.…”
Section: Synthesis and Electronic Structure Of A T-shaped Ni Complexsupporting
confidence: 80%
“…[31] Fluorinated metallacyclopentanes have been obtained by cyclodimerization of fluorinated ethenes (F), [22,[32][33][34][35][36][37][38] or cocyclodimerization of C 2 F 4 and C 2 H 4 (G), [39,40] on electron-rich metal centres. Their unusual reactivity [41][42][43][44] illustrates the potential of C 2 F 4 in the synthesis of valuable fluoroorganic compounds. [37,39,40] Only a few perfluorometallacycles with n ¼ 6 4 have been reported.…”
mentioning
confidence: 99%
“…An X‐ray diffraction study of 13 clearly demonstrated that the α‐CHPh carbon atom in 4 a was selectively protonated . Such reactivity of 4 a towards carboxylic acids is in contrast with that observed in [(SIPr)Ni(CF 2 ) 4 ], which underwent both α‐fluorine elimination and protonation …”
Section: Methodsmentioning
confidence: 58%
“…Burch and co‐workers reported pioneering work wherein α‐fluorine elimination in [(PEt 3 ) 2 Ni(CF 2 ) 4 ] was promoted by the addition of BF 3 ⋅Et 2 O to give (PEt 3 )(BF 4 )Ni[CF(PEt 3 )(CF 2 ) 3 ] as a result of the migration of one of the PEt 3 ligands to the transient fluorocarbene intermediate . Baker further demonstrated the transformation of [(SIPr)Ni(CF 2 ) 4 ] into perfluorocyclobutene and isolated its reaction intermediate (Scheme a) ,…”
Section: Methodsmentioning
confidence: 99%